Lagu Slompret-slompret Sebagai Pemicu Trance Pada Penari Jaran Kepang Turonggo Seto (Universitas Negeri Semarang, 2016)
There is always trance in the show of Jaran Kepang Turonggo Seto. Music is one of the way to become trance, it’s song Slompret-slompret. This research to purpose of; Describe forms of performance Jaran Kepang Turonggo Seto; Knowing how the process of trance the dancers Jaran Kepang Turonggo Seto; to know how the purpose of song Slompret-slompret. The conclusion is; the performing of Jaran Kepang Turonggo Seto consists of many factor, there is a story, dancer, dance property, costume, make up, dance, stage, sound system, and music illustration; before the trance is happen, the dancer of Jaran Kepang Turonggo Seto have to through of lelaku, sikap and ritual jamasan, it’s the adult dancer will; the fuction of the song Slompret-slompret use to medium dancer to trance. In the song have composition lyrics, composition, melody and garap ricikan.